Pelatihan Pembuatan Poster Edukasi Dan Koleksi Museum Bagi Anggota Ikatan Pemandu Museum Indonesia (IPMI) - Yusmawati Yusmawati; Nina Kusumawati; Sultan Himawan; Sri Wulandari (LPPM Universitas Bina Sarana Informatika, 2022)
Museums are one of the tourist destinations, especially educational and cultural tourism for the community. All resources in the museum including museum guides have an important role. In addition to being a guide, museum guide, and providing services for visitors, museum guides must also have other skills in communicating material or all things in the museum, including communicating in the form of posters that can be published. For two years, the world has been hit by the COVID-19 pandemic, and Indonesia is no exception. This pandemic has had a wide impact on all sectors of people's lives, including education and tourism. In 2022, the Ministry of Tourism and Creative Economy begins to launch a program to revive the slumped tourism industry. The Indonesian Museum Guides Association (IPMI) as a unifying forum and communication between museum guides in Indonesia welcomed this. One of them is by synergizing with Bina Sarana Informatika University in community service activities. In this activity, the lecturers who are members of the community service group help partners to provide training on making educational posters and museum collections for museum guides. This method of implementing Community Service activities is carried out online, through the zoom meeting application, due to the current pandemic situation in PPKM Level 3 status, so mass gathering in large numbers is not possible. The outputs of this activity include press releases and questionnaire results from both partners and participants.